Hukum Jual Beli Limbah Tambang Emas Perspektif Fatwa DSN MUI No. 110/DSN-MUI/IX/2017 Tentang Jual Beli (Studi Kasus di Desa Hutalombang Lubis Kecamatan Panyabungan Kabupaten Mandailing Natal) - Hasibuan, Toibah; Zahara, Fatimah (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The background of this research is that there is a gap in the implementation of the practice of buying and selling gold mining waste in Hutalombang Lubis Village, Panyabungan District, Mandailing Natal Regency. Whereas buying and selling is carried out by selling gold waste (dregs) in sacks which are not necessarily the result that is obtained without knowing the risks involved in the sale and purchase. This is not in accordance with Islamic Shari'at and does not meet the requirements for a sale and purchase object according to the perspective of DSN MUI Fatwa No. 110/DSN-MUI/IX/2017 concerning Sales and Purchase Contracts. If the Buyer gets the remaining Gold from processed Gold then the buyer will get a profit. However, on the other hand, if the buyer does not get the remaining gold from the land used for processing gold, then the buyer will definitely incur a loss. So the object being contracted contains an element of obscurity and is not in accordance with what is received by the buyer which results in a loss to one of the parties. The research method used is empirical juridical method, namely field research, using a qualitative approach and qualitative descriptive data analysis.